Immunology and bioinformatics analysis of injectable organic/inorganic microfluidic microspheres for promoting bone repair. (September 2022) - Xu, Yichang; Wu, Liang; Tang, Yunkai; Cai, Feng; Xi, Kun; Tang, Jincheng; Xu, Zonghan; Gu, Yong; Cui, Wenguo; Chen, Liang
Abstract: Organic/inorganic composites have advantages in promoting bone repair; however, early changes in the local immune response after material implantation and the mechanisms that affect the late osteogenesis have not been revealed systematically. Herein, we prepared injectable composite poly (l -lactic acid)/nano hydroxyapatite (PLLA/nHA) porous microspheres (MS@SL@nHA) using a microfluidic technology to explore the changes in the osteo-immune microenvironment and potential mechanisms using immunology and bioinformatics. Immunological analysis revealed that macrophages (Mφ) phagocytosed the nHA released from the composite microspheres, increased the proportion of M2 Mφ, regulated the early inflammatory response, exerted strong paracrine effects, and improved the osteo-immune microenvironment. Bioinformatics analysis showed that the signal transduction and adhesion ability were enhanced after Mφ activation, the inflammatory signaling pathways were inhibited, regulating the polarization direction, and the expression of cell growth factors was up-regulated to promote late osteogenesis. In vivo studies demonstrated that the composite microspheres effectively regulated Mφ polarization, and the paracrine secreted growth factors created a microsphere-centered osteogenesis pattern at the defect site. In conclusion, we successfully prepared injectable composite PLLA/nHA porous microspheres and systematically explored the osteogenesis-related mechanisms using immunological and bioinformatics analysis to provide theoretical evidence for bone repair materials that contribute to bone differentiation. Graphical abstract: Organic/inorganic composites have significant advantages in promoting bone repair. In this study, we prepared injectable PLLA/nHA composite microspheres and deeply explored their osteogenic mechanisms, which provided a certain supplement to the theoretical system of osteogenic differentiation of bone repair materials. Image 1